On the impact of Vertical Alignment of MoS2 for Efficient Lithium Storage - Victor Shokhen (Nature Portfolio, 2017)
Abstract Herein, we report energy storage devices, which are based on densely packed, vertically aligned MoS2 (VA-MoS2) or planar oriented MoS2 (PO-MoS2) and compare their electrochemical performances. The VA-MoS2 films have been processed by chemical vapor deposition (CVD) to reach unprecedented micron-scale thick films while maintaining the vertical alignment for the whole thickness. The VA-MoS2 and the PO-MoS2 films form a high-performance Li-ion electrode, reaching the theoretical limits of reversible capacity for this material (800 mAh/g; twice the specific capacity of graphite). The vertical alignment allows faster charge-discharge rates while maintaining a high specific capacity (C-rate measurements). Noteworthy, the reversible cycling of the Li-ion electrode also benefits from the vertical alignment. In this article, we present the full synthesis, structural and electrochemical characterization of VA-MoS2 along with the properties of PO-MoS2 to deconvolute the intrinsic properties of MoS2 from the influence of the layers’ orientation.